Analisis Istilah Khas dalam Wacana Politik Pemilu 2024 Implikasi Terhadap Pendidikan Politik Di Era Digital - Ariyanto, Zahy Riswahyudha; Sabardila, Atiqa (Universitas Lampung, 2023)
Political education for youth today is very important. It is necessary to innovate in the current era of information technology openness to achieve optimal political education goals. This research was conducted with the aims of (1) describing the typical terms (registers) and the meanings of terms in the 2024 election political discourse, (2) describing the strategies and processes of political education in the digital era through social media from the results of identification of typical terms (registers) and the meanings of terms in political discourse on the 2024 election. This type of research is descriptive qualitative. The data source for this research is the Discourse rubric of ideas about elections contained in Koran Tempo's digital news page. The data in this study are typical terms in the field of politics or political registers. Data was collected through the observing and note-taking method, then analyzed using the referential equivalent method. The validity of the data was tested using theoretical triangulation. The results are (1) Typical terms or political registers on the Koran Tempo digital news page are dominated by types of nouns or nouns, for example Cabinet, Period, Parliament, Sympathizers, Politicians, Ministers, Camps, Parties, Candidates, Legislators, there are also types of verbs or verbs namely Polarization, Authoritarianism, Press Conference, Controversy, Democracy, Electability, Coalition, Credibility, Integrity. Democratic. Campaign, (2) The findings in the first problem formulation are then used as political education content through social media for teenagers, especially students as innovation in an era of openness and advances in information technology. Pendidikan politik bagi remaja saat ini sangat penting dilakukan. Perlu diadakan inovasi di era keterbukaan teknologi informasi saat ini untuk mencapai tujuan pendidikan politik yang optimal. Penelitian ini dilakukan dengan tujuan (1) mendeskripsikan istilah khas (register) dan makna istilah dalam wacana politik pemilu 2024, (2) mendeskripsikan strategi dan proses pendidikan politik di era digital melalui media sosial dari hasil identifikasi istilah khas (register) dan makna istilah dalam wacana politik pemilu 2024. Jenis penelitian ini adalah kualitatif deskriptif. Sumber data penelitian ini adalah Wacana tentang pemilu yang terdapat dalam laman berita digital Koran Tempo. Data dalam penelitian ini adalah istilah khas dalam bidang politik atau register politik. Data dikumpulkan melalui metode simak dan catat, kemudian dianalisis menggunakan metode padan referensial. Keabsahan data diuji menggunakan trianggulasi teori. Hasilnya yaitu (1) Istilah khas atau register politik dalam laman berita digital Koran Tempo didominasi oleh jenis kata benda atau nomina, contoh Kabinet, Periode, Parlemen, Simpatisan, Politikus, Menteri, Kubu, Partai, Kandidat, Legislator, terdapat juga jenis kata kerja atau verba yaitu Polarisasi, Otoritarianisme, Konferensi Pers, Kontroversi, Demokrasi, Elektabilitas, Koalisi, Kredibilitas, Integritas. Demokratis. Kampanye, (2) Hasil temuan dalam rumusan masalah pertama, selanjutnya dijadikan konten pendidikan politik melalui media sosial bagi remaja khususnya pelajar sebagai inovasi di era keterbukaan dan kemajuan teknologi informasi. Keywords: Special terms, Politics, Education.